Implementação computacional de elementos de interface com elevada razão de aspecto para análise não linear de estruturas de concreto - Thais de Oliveira Azevedo (2019)
A finite element model is implemented and applied for nonlinear analysis of quasi brittle media in order to describe the behavior of the media even after the crack opening. The issue of degradation is dealt with formulations based on the Continuum Strong Discontinuity Approach - CSDA, which are used to express the kinematics of the interface element. The fragmentation of the standard finite element mesh in order to introduce elements with a high aspect ratio, allows the analysis of the jump in the displacement field through a continuum constitutive model, consistent with the strong discontinuity mode. The implementation was performed in the INSANE computer system (INteractive Structural ANalysis Environment), developed in UFMG's Department of Structural Engineering, which has a wide range of constitutive models that can be used for the described modeling. In the current work, a smeared cracking model and an isotropic damage model were chosen for the description of the media. The use of interface elements, enables the treatment of the crack propagation problem without the necessity of prior definition of its path or the redefinition of the mesh during the analysis, as also the possibility of the description of multiple simultaneous cracks. Numerical simulations were carried out to validate the implemented model.